Venom-microbiomics of eight species of Neotropical spiders from the Theraphosidae family - Viquez, Carlos (2024)
Aim: Tarantulas are one of the largest predatory arthropods in tropical regions. Tarantulas though not lethal to humans, their venomous bite kills small animals and insect upon which they prey. To understand the abiotic and biotic components involved in Neotropical tarantula bites, we conducted a venom-microbiomics study in eight species from Costa Rica. Methods and results: We determined that the toxin profiles of tarantula venom are highly diverse using shotgun proteomics; the most fre- quently encountered toxins were ω-Ap2 toxin, neprilysin-1, and several teraphotoxins. Through culture-independent and culture-dependent meth- ods, we determined the microbiota present in the venom and excreta to evaluate the presence of pathogens that could contribute to primary infections in animals, including humans. The presence of opportunistic pathogens with hemolytic activity w as observ ed, with a prominence of Stenotrophomonas in the venoms. Other bacteria found in venoms and excreta with hemolytic activity included members of the genera Serratia , B acillus , A cinetobacter , Microbacterium , and Morganella . Conclusions: Our data shed light on the venom- and gut-microbiome associated with Neotropical tarantulas. This information may be useful for treating bites from these arthropods in both humans and farm animals, while also providing insight into the toxins and biodiversity of this little-e xplored microen vironment.